ETNOBOTANI TUMBUHAN DI DESA SERUMPUN KABUPATEN SAMBAS YANG DIMANFAATKAN SEBAGAI KOSMETIK - Sisi Arlina; Syamswisna Syamswisna; Hayatul Fajri (Scripta Biologica, 2023)
People of Serumpun village Sambas district usually use plants as traditional cosmetics. Especially, for betangas (traditional sauna) and bekasai (traditional scrub). The plant used as a cosmetic has been used for generations and maintained by people of Serumpun village to this day. This research aimed to observed the plant traditionally used as a cosmetic in Serumpun village Sambas district. Forty-seven species from 30 families were used as the cosmetic source. The most family used for cosmetic are Rutaceae and Zingiberaceae. Fruit is the most plant part used for cosmetics, and people of Serumpun village primarily use the plant for skincare.